Electromagnetic scattering computation methods for very small spheroidal dust particles: theory and applications - Bashir, Saad Osman; Musa, A. A.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran (IDOSI Publications, 2013)
This paper discusses the effect of propagation of electromagnetic waves through a cloud of very small particles. The size of these particles is normally less than 0.2 mm in radius, much smaller than the microwave wavelength; therefore it is possible to avoid laborious computation by using approximations. In this work we have checked the Rayleigh theory (Rayleigh scatterer) against a full solution of Maxwell’s main equations through a point matching technique (PMT). The agreement between Rayleigh approximations and PMT for these very small particles is found to be good. These results have been used in quantifying some telecommunication channel impairments